Maternal Nicotine Induces Collagen Type IV Changes in the Mice Lung Parenchyma and its Vessels - Mohammadi, Shabnam (National Research Institute of Tuberculosis and Lung Disease, 2011)
BACKGROUND: One of the undesirable effects of maternal nicotine exposure during pregnancy is pulmonary hypertension. Since nicotine binds to its receptors on pulmonary vessels the hypothesis of this research was the possible structural changes that nicotine may cause on newborn vessels. MATERIALS AND METHODS: Twenty-four female BALB/c mice were mated and finding vaginal plug was assumed as day zero of pregnancy. Pregnant mice were divided into 2 experimental and 2 control groups. Experimental group 1 received 3 mg/kg nicotine intraperitoneally from day 5 of gestation until the last day of pregnancy. Experimental group 2 received the same amount of nicotine during the same gestational days as well as the first 2 weeks after birth (lactation). The control groups received the same volume of normal saline during the same periods. At the end of exposure times, all the newborns (experimental and control) were anesthetized, their lungs were removed and immunohistochemical studies were carried out for tracing collagen. RESULTS: Our findings indicated that collagen reaction in the bronchial basement membrane (BBM) and extracellular matrix (ECM) of the lung parenchyma in experimental groups increased significantly compared to the control groups but these changes were not observed in BM of lung vessels in the experimental groups. CONCLUSION: These data indicate that nicotine exposure during pregnancy does not cause a significant change in collagen type IV in BM of lung vessels. But this does not mean that other types of collagen fibers do not indicate change because the wall thickness of pulmonary vessels in experimental groups increased significantly compared to the control groups.